Comparison of The Accuracy of Smartimu and Images Applications in Determining The Grade of Bone Loss As Seen On Periapical Radiographs - Amanah Pertiwisari; Yusrini Selviani; Nur Rahmah Hasanuddin; Taufan Lauddin; Audy Anugrah (Lembaga Penelitian Universitas YARSI, 2026)
Introduction: Periodontal disease is one of the most common oral health problems with significant global prevalence. Periapical radiography is used as the primary tool for diagnosing alveolar bone loss in periodontal disease. In the digital era, software such as smarTimu and ImageJ offer innovative methods for accurately determining the grade of bone loss. Objective: This study aims to compare the accuracy of smarTimu and ImageJ applications in determining the grade of bone loss based on periapical radiograph analysis. Materials and Methods: This study used an analytical observational method with a cross-sectional design with a sample of internship students at the RSIGMP FKG Universitas Muslim Indonesia who met the inclusion criteria. Periapical radiographic data were analyzed using smarTimu and ImageJ. Measurement accuracy was compared with the gold standard. Results: The Mann-Whitney test showed a p-value of 0.000, which is less than 0.05, indicating a significant difference in the measurement grades between the smarTimu and ImageJ applications. Conclusion: There is a comparison of the accuracy of the smarTimu application with ImageJ in determining bone loss grades based on periapical radiographs.